2020
DOI: 10.1111/ajr.12599
|View full text |Cite
|
Sign up to set email alerts
|

Using firefighters as medical first responders to shorten response time in rural areas in Sweden

Abstract: Objective To map out and describe an earlier response by using firefighters as medical first responders on while waiting for the ambulance and first incident person assignments focusing on frequency, event time and survival >30 days after performed cardiopulmonary resuscitation. Design Retrospective descriptive design. Setting Ambulance service in a county of southern Sweden with a population of 200 000 inhabitants (23/km2). Participants Data were collected from four data systems within different organizations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This encourages conducting further studies per country to help healthcare officials enhance their interventions. In this context, a previous study indicated that using firefighters as medical first responders enhances pre-hospital time and patient outcomes in Sweden [ 55 ]. Moreover, in South Korea, the National Ambulance Service suggested that EMS for specific events (like cardiac arrest) might be conducted by moderate care ambulances and non-front-line officers to reduce response time, as such events might not require high levels of training and management resources, which might save time in those situations [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This encourages conducting further studies per country to help healthcare officials enhance their interventions. In this context, a previous study indicated that using firefighters as medical first responders enhances pre-hospital time and patient outcomes in Sweden [ 55 ]. Moreover, in South Korea, the National Ambulance Service suggested that EMS for specific events (like cardiac arrest) might be conducted by moderate care ambulances and non-front-line officers to reduce response time, as such events might not require high levels of training and management resources, which might save time in those situations [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…( 2019 ) and Svensson et al. ( 2020 ) Shuster and Keller ( 1993 ), White et al. ( 1998 ), Jermyn ( 2000 ), Smith et al.…”
Section: Pre-ems Servicesmentioning
confidence: 98%
“…The European Resuscitation Council guidelines emphasise the importance of using technology such as text messages or smartphone applications to alert voluntary first responders (VFRs) to suspected OHCAs and improve the rate of bystander CPR [ 5 ]. This is important, as prolonged response time for EMS arrival is common [ 6 , 7 ], and time to CPR significantly affects survival outcomes [ 8 , 9 ]. In Sweden, the ambulance response time in the case of OHCA has significantly increased over time, from 5 min in the early 1990s to 12 min in 2020 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%